Developing Tutorial Learning Video To Enhance Students Practical Skill of Betawi Folk Dance Cokek Sipatmo In Cultural Arts Subject For Middle School Students Grade VIII - Sasih, Nana Sunar; Syahrial, Zulfianti; Rusmono, Rusmono (International Journal for Educational and Vocational Studies, 2020)
This study which is aimed to develop a learning video, entitled "Developing Tutorial Learning Video to Enhance Students Practical Skill of Betawi Folk Dance Cokek Sipatmo in Cultural Arts Subject for Middle School Students Grade VIII " and is designed for Cultural Arts Education particularly dance for middle school students which has proven its effectiveness to improve the final grades of middle school students. The research participants were Al Azhar Syifa Budi Junior High School students in Jakarta. This research and development followed the stages of Lee and Owens' development. The stages in developing a video tutorial are: (1) conducting a preliminary analysis, (2) conducting a front-end analysis consisting of audience analysis, technology analysis, task analysis, media analysis; (3) Design; (4) Development: one to one production and test processes; (5) Implementation; (6) Evaluation (Validation from content expert, media expert, instructional design expert). Video tutorials can be accessed online for everyone at anytime in any place. The result of this study indicated that the video tutorial is beneficial in the learning process of the Betawi Cokek Sipatmo Dance Practice in the subject of Cultural Arts as evidenced by the increase in post-test scores compared to the pre-test scores.